2005
DOI: 10.1080/10893950500357970
|View full text |Cite
|
Sign up to set email alerts
|

Thin Film Non-Noble Transition Metal Thermophysical Properties

Abstract: The transient thermoreflectance (TTR) technique coupled with a pump-probe experimental setup enables the observation of thermal transport phenomena on a sub-picosecond time scale. The reflectance from non-noble transition metals (at least one unoccupied d-orbital in the conduction band) can be shown to have a linear dependence when compared to small changes in the electron and lattice temperatures. This thermal dependence can be combined with the parabolic two step (PTS) model to enable measurement of the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
58
2

Year Published

2007
2007
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 18 publications
4
58
2
Order By: Relevance
“…The best fit to the experimental data was obtained for G ¼ 9 Â 10 16 W/m 3 K with an uncertainty of 62 Â 10 16 W/m 3 K. When values of G are within the error bar, the simulated and experimental X-ray diffraction efficiencies are in agreement, but when values of G lie outside the error bar, the simulation results start to deviate significantly from the experiment. The value of G is lower than those measured previously by Beaurepaire et al, 21 Wellershoff et al, 22 Saito et al, 23 Caffrey et al, 15 and Hopkins et al 24 (see Table II). In Table II it can be seen that a wide range of film thickness and fluencies have been used for the previous studies.…”
contrasting
confidence: 52%
See 2 more Smart Citations
“…The best fit to the experimental data was obtained for G ¼ 9 Â 10 16 W/m 3 K with an uncertainty of 62 Â 10 16 W/m 3 K. When values of G are within the error bar, the simulated and experimental X-ray diffraction efficiencies are in agreement, but when values of G lie outside the error bar, the simulation results start to deviate significantly from the experiment. The value of G is lower than those measured previously by Beaurepaire et al, 21 Wellershoff et al, 22 Saito et al, 23 Caffrey et al, 15 and Hopkins et al 24 (see Table II). In Table II it can be seen that a wide range of film thickness and fluencies have been used for the previous studies.…”
contrasting
confidence: 52%
“…In the studies cited, different methods and observables have been used. Beaurepaire et al 21 detected electron and spin temperatures, Caffrey et al 15 and Hopkins et al 24 detected electron and lattice temperatures whereas the study by Wellershoff et al 22 is based on damage thresholds. The conditions in the measurement by Saito et al 23 mostly resemble ours in terms of film thickness and method, since they also observed an acoustic response in the lattice.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13,[15][16][17] However, there is growing experimental evidence that the applicability of the constant G-factor is limited to a low intensity laser pulses. [18][19][20] Kaganov et al 21) proposed a theoretical model of the G-factor with electron relaxation time that is defined as the inverse of the electron-phonon collision frequency and usually assumed to be proportional to 1=T e , forcing the G-factor to be constant.…”
mentioning
confidence: 99%
“…3.2, it is clear that if the metal film does not strongly adhere with the nonmetal substrate, the substrate dependence in the e-p coupling no longer exists. To further understand the various scattering mechanisms contributing to h ei , measurements are repeated for samples with is chosen due to the fact that the e-p coupling factor for Pt has been reported to be similar to the value for Ti [120] and also because Pt does not adhere strongly to the nonmetal substrates. Figure. resistance (compared to the resistance due to the slow e-p equilibration in the Au layer).…”
Section: Experimental Considerationsmentioning
confidence: 99%